PENGARUH PENGETAHUAN KEWIRAUSAHAAN DAN PEMANFAATAN MEDIA SOSIAL TERHADAP MINAT BERWIRAUSAHA SISWA KELAS XI PEMASARAN SMK NEGERI 1 MEDAN - Sylvia Amanda; Ivo Selvia Agusti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
entrepreneurial interest among eleventh-grade students majoring in Marketing at SMK Negeri 1 Medan. This study used a quantitative approach with an ex-post facto method. The study population consisted of 67 eleventh-grade students majoring in Marketing at SMK Negeri 1 Medan. The sampling technique used total sampling, so the entire population served as the research sample. Data collection was carried out by distributing questionnaires that had been tested for validity and reliability. Data analysis was performed using SPSS 25, which included validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, partial tests (t-tests), simultaneous tests (Ftests), and coefficient of determination (R²) tests. The results showed that entrepreneurial knowledge had a positive and significant effect on entrepreneurial interest, as evidenced by a calculated tvalue of 9.631 > ttable of 1.998 and a significance value of 0.000 < 0.05. Furthermore, the use of social media also has a positive and significant effect on entrepreneurial interest, as indicated by the calculated tvalue of 8.416 > ttable of 1.998 with a significance value of 0.000 < 0.05. Simultaneously, entrepreneurial knowledge and social media utilization have a positive and significant effect on entrepreneurial interest, with an Fvalue of 80.283 > Ftable of 3.14 and a significance value of 0.000 < 0.05. In addition, the results of the determination coefficient test show an R Square value of 0.715, which means that 71.5% of the variation in students' entrepreneurial interest can be explained by entrepreneurial knowledge and social media utilization, while the remaining 28.5% is influenced by other factors not examined in this study. The results of this study indicate that Entrepreneurial Knowledge and Social Media Utilization have a positive and significant effect on Entrepreneurial Interest of 11th grade students majoring in Marketing at SMK Negeri 1 Medan.